ELIMINASI PINEAPPLE MEALYBUG WILT-ASSOCIATED-VIRUS (PMWaV) DARI TANAMAN NANAS DENGAN HOT WATER TREATMENT - Mimi Sutrawati; Gede Suastika; Sobir Sobir (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[ELIMINATION OF Pineapple Mealybug Wilt-associated Virus (PMWaV) FROM PINEAPPLE PLANT BY HOT WATER TREATMENT]. Mealybug wilt of pineapple (MWP) is a devastating disease found in all the major pineapple growing regions. Closterovirus particles can be detected in both MWP symptomatic and asymptomatic pineapple. Rogue of symptomatic plants is the simplest method of controlling MWP disease, but this method is less effective as PMWaV might remains at asymptomatic plants. Use of pesticide to control mealybug and ants is not efficient and high cost. The research was conducted to develop elimination method for PMWaV-free plant by hot water treatment. PMWaV infected plant parts (leave, stem, crown) were exposed to two hot water treatments, consisting of 35 ºC for 24 hour as pre-treatment and immediately followed by hot water treatment either 56 ºC for 60 minute or 58 ºC for 40 minute in a water bath. The infected plant without hot water treatment served as the positive control, and healthy plant without hot water treatment as the negative control. PMWaV infection could be eliminated from propagative material through hot water treatment 58 ºC 40 minute in a water bath without decrease propagative material viability.